(untitled) (The Pakistan Development Review, 2008)
ENERGY SECURITY 1.1. Energy security has become the burning topic of the day both in country specific and international terms. Many consider that the new alignments in geopolitics are strongly influenced by the search for energy security which may be defined as “dependable and affordable energy necessary for an economy.” It is even claimed that in terms of strategic importance energy security is second only to food security. Given the shortage of energy we are facing and the national debate on its cost and affordability, there is no doubt consensus that we have an Energy Crisis in the country and our Energy Security is at risk.